Desenvolvimento e caracterização de nanopartículas lipídicas contendo topotecano - SOUZA, Leonardo Gomes (2010)
Topotecan (TPT), hydrophilic semisynthetic analogue of camptothecin, is a topoisomerase I inhibitor anticancer agent. Encapsulation of TPT in nanocarriers can protect him from inactivation on plasmatic pH and P-glycoprotein (P-gp) mediated resistance. In this study, solid lipid nanoparticles (SLN) were produced by three different methods: cold high pressure homogenization (CHPH), double emulsion prepare (DEMP) and microemulsion dilution (MMD). Derivative systems from NLS, nanostructured lipid carriers (NLC) were produced only by MMD. Temperature proved to be a limiting factor in producing nanoparticles loaded TPT and must be strictly controlled. Nanoparticles produced by MMD (SLN and NLC) presented best encapsulation efficiency, drug loading and particle size distribution. These particles presented 150 nm average diameter, 0.2 PdI and -45 mV average zeta potential. Despite the hydrophilic drugs encapsulation to be a hard work, lipid nanoparticles loaded TPT presented 6% drug loading and an encapsulation efficiency biggest then 95%. Encapsulation of TPT in lipid nanoparticles sustained drug release by 12 hours and protected the drug from degradation at pH 7,4 at 37°C. Drug nanoencapsulation also increased his citotoxicity on K562 leucemic cells at 2 and 24 hours. There weren t differences between NLC and SLN on release, citotoxicity and stability studies. Threalose was an efficient cryoprotector on lyophilization of SLN and NLC loaded TPT. Lyophilizates NLC and SLN with 15% of threalose stayed stable almost for 30 days. Nanostructured lipid carriers with high topotecan chloridrate loading obtained in this work presented potential to improve clinical efficacy associated with parenteral administration of this important citotoxic drug.